Media Video Seni Budaya : Materi Seni Rupa Dua dan Tiga Dimensi Kelas II SDN 05 Pemulutan - Umirta, Tasya; Arni, Yusni; Apriani, Dinda Rizki; Diningrum, Aliyah; Sinurat, Rita (ALACRITY : Journal of Education, 2024)
This study aims to create a canva-based learning media so that students understand more deeply about two and three dimensional fine arts and to develop knowledge and skills in the field of two and three-dimensional fine arts, more precisely in class II of SDN 05 Pemulutan. The type of research used in the two and three-dimensional fine arts learning video for class II of elementary school is canva-based visual research. Visual research involves images, diagrams, and other visual elements to communicate information and ideas. The conclusion that can be drawn from testing the canva-based learning video media is that canva is an effective and easy-to-use tool for creating attractive and informative visuals for the purpose of learning two and three-dimensional fine arts for class II of SDN 05 Pemulutan.